1996
DOI: 10.1093/ejo/18.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial morphology in young patients With Turner syndrome

Abstract: The craniofacial morphology of 33 Turner syndrome patients, aged 7-16.7 years, was evaluated by standard cephalometric methods. The sample was subdivided according to karyotype and 72 normal girls aged 7.1-16.1 years served as controls. The size of the calvarium and face was generally smaller in the Turner group than in the controls. The morphology was characterized by a flattened cranial base angle, a marked reduction in posterior cranial base length, facial retrognathism and short and posteriorly rotated jaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Previous studies demonstrated that a shortening of the cranial base during development leads to a number of mid‐facial abnormalities. For example, the retrognathic facial profile characteristic of Cretinism, Turner syndrome, and Down's syndrome is due to reduced cranial base length (Israel et al, ; Jensen, ; Rongen‐Westerlaken et al, ; Midtbo et al, ; Andersen et al, ; Quintanilla et al, ). Similar trends are also identified in Klinefelter syndrome and Williams's syndrome (Mass and Belostoky, ; Brkic et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that a shortening of the cranial base during development leads to a number of mid‐facial abnormalities. For example, the retrognathic facial profile characteristic of Cretinism, Turner syndrome, and Down's syndrome is due to reduced cranial base length (Israel et al, ; Jensen, ; Rongen‐Westerlaken et al, ; Midtbo et al, ; Andersen et al, ; Quintanilla et al, ). Similar trends are also identified in Klinefelter syndrome and Williams's syndrome (Mass and Belostoky, ; Brkic et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Midtbø et al indicated that a deviating pattern of craniofacial size and morphology originates in the fetal period when the primary cartilages form the craniofacial skeleton and already exists since childhood …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the mosaic and isochrome for long arm of chromosome showed the same pattern of malocclusion with varying degrees. [8] Similar study by Cockanye postulated on X-linked recessive gene in families where males alone were affected and a typical phenotype of the disease was found. [12] Thus we studied structural aberrations of the X-chromosome using karyotyping.…”
Section: Discussionmentioning
confidence: 60%
“…Various authors have studied karyotyping in patients with Turner's syndrome,[8] Cri-du-chat syndrome[9] and found changes at chromosomal level. As ED is also a hereditary condition with abnormality in the human genome, karyotyping can be used to locate the abnormal chromosome.…”
Section: Introductionmentioning
confidence: 99%